2021
DOI: 10.3389/fmolb.2020.577246
|View full text |Cite
|
Sign up to set email alerts
|

Differential Progression of Motor Dysfunction Between Male and Female Fragile X Premutation Carriers Reveals Novel Aspects of Sex-Specific Neural Involvement

Abstract: Expansions of the CGG repeat in the non-coding segment of the FMR1 X-linked gene are associated with a variety of phenotypic changes. Large expansions (>200 repeats), which cause a severe neurodevelopmental disorder, the fragile x syndrome (FXS), are transmitted from the mothers carrying smaller, unstable expansions ranging from 55 to 200 repeats, termed the fragile X premutation. Female carriers of this premutation may themselves experience a wide range of clinical problems throughout their lifespan, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 77 publications
2
22
0
Order By: Relevance
“…Notably, the Basal Respiration Rate, ATP synthesis and Non-mitochondrial bioenergetics components are also highly correlated with the SCL90 GSI total, and /or Anxiety and Depression domains. This finding is not unexpected considering that neuropsychiatric features have been a major issue in both FXTAS and non-FXTAS carriers, especially females (6,29,(80)(81)(82)(83). Consistent with the extent of these problems across carrier categories, in this study we found significant correlations of these neuropsychiatric features with bioenergetic changes in the FXTAS subgroup, as well as in the combined (FXTAS and non-FXTAS) sample of PM carriers.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Notably, the Basal Respiration Rate, ATP synthesis and Non-mitochondrial bioenergetics components are also highly correlated with the SCL90 GSI total, and /or Anxiety and Depression domains. This finding is not unexpected considering that neuropsychiatric features have been a major issue in both FXTAS and non-FXTAS carriers, especially females (6,29,(80)(81)(82)(83). Consistent with the extent of these problems across carrier categories, in this study we found significant correlations of these neuropsychiatric features with bioenergetic changes in the FXTAS subgroup, as well as in the combined (FXTAS and non-FXTAS) sample of PM carriers.…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with the extent of these problems across carrier categories, in this study we found significant correlations of these neuropsychiatric features with bioenergetic changes in the FXTAS subgroup, as well as in the combined (FXTAS and non-FXTAS) sample of PM carriers. This result calls for more attention to these well-documented and prevalent neuropsychiatric problems; since they occur both in obviously affected and non-affected PM carriers, the need for early intervention is emphasised, following our earlier recommendations for the female carriers (6). Moreover, both measures of executive functioning (Matrix Reasoning and Digit Span Backward), which are known to be affected early in the non-FXTAS carriers, are significantly correlated with the elevated bioenergetics and cellular stress response components in this subgroup.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Especially considering that the postulated modifying effect of this parkinsonian genome, this is more likely to only apply to subpopulations of individuals in respective diagnostic categories who also manifest parkinsonian features in addition to their specific FXTAS or ET phenotypes. This assumption is substantiated by the common (in~30%) occurrence of parkinsonian features in FXTAS, combined with the lack of ameliorating effect of the normal FMR1-X chromosome on the parkinsonian (UPDRS) score in a cohort of the female PM carriers (Loesch et al, 2021). On the other hand, the reported excess of carriers of GZ alleles in several independent PD cohorts (Hall et al, 2011;Loesch et al, 2009;Loesch et al, 2013;Loesch et al, 2018) indicates a possible combined effect of these alleles and the assumed PD risk genotype.…”
Section: Discussionmentioning
confidence: 97%